PENGARUH PENGETAHUAN PAJAK DAN KESADARAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI RUMAH BUMN KOTA BOGOR DENGAN E-BILLING SEBAGAI VARIABEL MODERASI - Nurul Hidayah, Asshafa Dwia; Lasmana, Andy; Hambani, Susy (Komunitas Manajemen Kompetitif, 2025)
This research is motivated by the low level of compliance of MSME taxpayers in making tax payments on time, even though various facilities have been provided by the government, one of which is through the application of e-billing. The purpose of this study is to examine the effect of tax knowledge and tax awareness on MSME taxpayer compliance at the Bogor City Rumah BUMN with e-billing as a moderating variable. The variables were developed based on the Theory of Planned Behavior (TPB) theory. The population in this study are MSMEs under the auspices of Rumah BUMN that have used e-billing in their tax payments. Determination of the sample of this study using the Slovin formula, with a total of 267 MSME respondents. Data collection was carried out by distributing questionnaires using Google Form and directly to MSMEs who were respondents. The data processing tool used SmartPLS Version 3.0 by testing the inner and outer models. The results showed that tax knowledge has a positive and significant effect on taxpayer compliance, tax awareness has a positive and significant effect on taxpayer compliance, and e-billing has a positive effect on taxpayer compliance. In addition, e-billing moderates the relationship between tax knowledge and tax awareness on taxpayer compliance, but the moderation that occurs weakens the relationship between tax awareness and taxpayer compliance Keywords: Tax knowledge, tax awareness, taxpayer compliance, e-billing